Differential Cryptanalysis ofLightweight Block Ciphers SLIM andLCB - Chan Y.Y.; Khor C.-Y.; Teh J.S.; Teng W.J.; Jamil N. (Springer Science and Business Media Deutschland GmbH, 2023)
Cryptography; Heuristic methods; Security of data; Concrete securities; Differential cryptanalysis; LCB; Lightweight block ciphers; Network structures; Secret key; Security analysis; SLIM; Substitution-permutation networks; Ultra lightweights; Lyapunov methods